Environmental-based learning and joyful learning experiences in elementary education - Adolina Velomena Samosir Lefaan; Dhanu Priyo Widodo; Orlando Antonio Selly (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This study examines the utilization of the surrounding environment as a contextual learning medium in fostering joyful learning experiences among elementary school students. A qualitative descriptive approach was employed at SD Negeri Inpres Pantai Enggros. Data were collected through classroom observations, semi-structured interviews, and documentation involving five teachers and fifteen students from grades IV–VI selected through purposive sampling. The data were analyzed using thematic analysis supported by coding, categorization, interpretation, and triangulation procedures to ensure trustworthiness. The findings indicate that environmental-based learning creates meaningful, interactive, and enjoyable learning experiences for students. The use of the surrounding environment as an authentic learning medium enhances students’ learning enthusiasm, curiosity, emotional engagement, collaboration, and active participation. Direct interaction with real-life environmental contexts enables students to construct knowledge through exploration, observation, and social interaction. The study also highlights the crucial role of teachers as facilitators in designing flexible, student-centered learning environments that support joyful learning. This study contributes to the literature by integrating environmental-based learning and joyful learning perspectives within elementary education. It proposes a conceptual relationship between environmental-based learning practices and the development of joyful learning experiences, offering insights for implementing contextual and engaging learning environments in elementary schools.